EXPLORING INVESTIGATIVE PROCESSES: A COMPARATIVE STUDY OF LEGAL LIMITATIONS IN INDIA AND INTERNATIONAL CONTEXTS - Singh, Janmejay; Mishra, Taru (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The article Exploring Investigative Processes: A Comparative Study of Legal Limitations in India and International Contexts, looks at how law enforcement responds to major crimes, focusing on the legal powers, obstacles, and innovations in technology that impact these investigations. It highlights issues related to witness intimidation and procedural delays, seeking for transparency using openness procedures such as face cameras. This research highlights the need for carrying out comprehensive and unbiased investigations—including evidence collection, witness interviews, and forensic analysis—to avoid convictions of justice. The article, which explores the responsibilities of law enforcement, forensic experts, and the judiciary, as well as establishing advancements in technology and data privacy, advocates for increased transparency and efficiency in order to maintain public trust in the judicial system. The criminal justice system’s cornerstone is the investigative process, which determines how court cases progress. Investigations are used to determine facts, collect evidence, and provide the groundwork for judicial and prosecution measures. However, legal restrictions frequently make investigation procedures less effective. This article focuses at these restrictions in the Indian context and compares them to global standards in order to find areas that might use modification.